Mitophagy and NAD+ inhibit Alzheimer disease. Issue 6 (3rd June 2019) - Fang, Evandro F.
ABSTRACT: Our latest publication on the inhibition of Alzheimer disease (AD) through mitophagy consolidates the 'defective mitophagy hypothesis of AD etiology'. Dementia (majorly AD) affects over 50 million people worldwide, and for AD there is no cure. AD leads to progressive loss of cognition, and pathological hallmarks of AD include aggregates of amyloid-β peptides extracellularly and MAPT (microtubule associated protein tau) intracellularly. However, there is no conclusive link between these pathological markers and cognitive symptoms. Anti-AD drug candidates have repeatedly failed, which led us to investigate other molecular etiologies to guide drug development. Mitochondria produce the majority of cellular ATP, affect Ca 2+ and redox signaling, and promote developmental and synaptic plasticity. Mitochondrial dysfunction and accumulation of damaged mitochondria are common in brain tissues from AD patients and transgenic AD animal models, but the underlying molecular mechanisms are not fully understood. Damaged mitochondria are removed through multiple pathways, the major 2 being mitophagy and the ubiquitin proteasome pathway. Mitophagy is essential for clearance of damaged mitochondria to maintain mitochondrial homeostasis, ATP production, and neuronal activity and survival. These pieces of evidence converge on the 'defective mitophagy hypothesis of AD etiology', and the current cross-species study provides strong support for this hypothesis.